Collision of extensive exocrine and neuroendocrine neoplasms in multiple endocrine neoplasia type 1 revealed by cytogenetic analysis of loss of heterozygosity: A case report. (28th August 2013) - Moriyoshi, Koki; Minamiguchi, Sachiko; Miyagawa‐Hayashino, Aya; Fujimoto, Masakazu; Kawaguchi, Michiya; Haga, Hironori
<x xml:space="preserve">Abstract</x> The combination of exocrine and neuroendocrine neoplasms is rarely found in the pancreas. These combined lesions vary from a clonal tumor with mixed differentiation to the incidental co‐existence of two or more independent tumors, but the differential diagnosis is sometimes difficult. Here we report a case of multiple endocrine neoplasia type 1 (MEN1) with extensive ductal and neuroendocrine neoplastic changes. These two types of tumors admixed markedly in some parts, which made it difficult to determine the pathological diagnosis based on histological findings. Cytogenetic analysis showed that loss of heterozygosity (LOH) of the MEN1 locus exists in neuroendocrine but not in exocrine neoplasms, indicating that independent mechanisms of tumorigenesis may occur in these two types of tumors. This case shows the usefulness of cytogenetic analysis for the diagnosis of combined tumors of the pancreas. Extensive exocrine neoplastic change, including pancreatic intraepithelial neoplasia (PanIN) in virtually all pancreatic ducts and a focus of intraductal papillary mucinous neoplasm (IPMN) with focal invasion, was a distinguishing feature of the present case. The possible association of ductal tumorigenesis and a MEN1 background is discussed.